Governance in Health Care Delivery : Raising Performance - Lewis, Maureen; Pettersson, Gunilla (2012)
The impacts of health care investments in developing and transition countries are typically measured by inputs and general health outcomes. Missing from the health agenda are measures of performance that reflect whether health systems are meeting their objectives; public resources are being used appropriately; and the priorities of governments are being implemented. This paper suggests that good governance is central to raising performance in health care delivery. Crucial to high performance are standards, information, incentives and accountability. This paper provides a definition of good governance in health and a framework for thinking about governance issues as a way of improving performance in the health sector. Performance indicators that offer the potential for tracking relative health performance are proposed, and provide the context for the discussion of good governance in health service delivery in the areas of budget and resource management, individual provider performance, health facility performance, informal payments, and corruption perceptions. What we do and do not know about effective solutions to advance good governance and performance in health is presented for each area, drawing on existing research and documented experiences.